2010
DOI: 10.1111/j.1399-3054.2010.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased gelling agent concentration promotes somatic embryo maturation in hybrid larch (Larix×eurolepsis): a 2‐DE proteomic analysis

Abstract: An integrated physiological and proteomic approach was used to investigate the effects of high gellan gum concentration in the medium during maturation of somatic embryos (SE) of hybrid larch, by comparing embryos incubated in media with a high gellan gum concentration (8 g l(-1) ) and the standard concentration (4 g l(-1) ) after 1, 3, 6 and 8 weeks of maturation. Because of the reduced availability of water in the 8 g l(-1) medium, the cultured embryos had a lower osmotic water potential (Ψπ) and water conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
(70 reference statements)
1
41
1
Order By: Relevance
“…Our results are not in accordance with Teyssier et al (2011) when they reported a higher level of this type of proteins only in somatic embryos produced under high water availability conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results are not in accordance with Teyssier et al (2011) when they reported a higher level of this type of proteins only in somatic embryos produced under high water availability conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…close relatives, according to SwissProt database (Table 1). The fact that for one spot (enolase) more than one protein was identified may be caused by the degradation products of some proteins (Teyssier et al 2011) or by the presence of multiple isoforms of a protein (Lippert et al 2005). The presence of protein isoform with different expressionpatterns during seed maturation has already been reported in barley (Finnie et al 2006).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, few studies have focused on the impact of temperature (Kvaalen & Johnsen, 2008), and the effect of different concentrations of agar in the culture medium has been studied mostly at maturation stage (Teyssier et al, 2011;Morel et al, 2014). In this sense, in our laboratory García-Mendiguren et al (2016) described in Pinus radiata (D. Don) that different temperatures and water availability conditions at initiation affected subsequent phases of SE; however, this effect on subsequent phases of the process disappeared when different environmental conditions were applied at proliferation.…”
Section: Introductionmentioning
confidence: 91%